Analysis of the Utilization of the Samagov Application Using the System Usability Scale (SUS) Method at the Samarinda City Department of Communication and Information - Hidayat, Jekri; Fahmi, Muhammad; Madani, Muhammad Nur (Sebatik, 2025)
The Government of Samarinda City has undertaken digital transformation efforts and launched the Samagov application as part of the Samarinda Smart City initiative, where the success of its implementation largely depends on users’ perceptions of its Usability. If the application is difficult to operate, public engagement will be hindered, resulting in suboptimal utilization. Therefore, measuring Usability is essential to understand whether Samagov meets users’ expectations and needs. This study employs a quantitative approach using surveys and the System Usability Scale (SUS) questionnaire to evaluate the Usability level of the Samagov application. The SUS method, developed by John Brooke in 1986, consists of a ten-item questionnaire designed to assess users’ perceptions of system ease of use. Data were collected by distributing an online questionnaire via Google Form to 40 respondents, consisting of internal staff of Diskominfo and external users who had accessed Samagov services. The calculation process involved subtracting 1 from odd-numbered items, subtracting 5 from even-numbered items, summing all scores, and then multiplying the total by 2.5. The average SUS score obtained from 40 respondents for the Samagov application was 62.56. Based on SUS interpretation scales, a score of 51.7–62.6 falls into grade D with the adjective rating “OK” at the 15–59th percentile. An “OK” score indicates that the application has relatively low Usability and requires improvements in user comfort and ease of use. The interpretation also suggests that while the application is fairly good, it has not yet reached the expected Usability standards for Samagov users. This study concludes that the Usability of the Samagov application, as measured by the SUS method, is rated as “Good” but highlights the need for further improvements in user comfort and ease of use. The SUS method has proven effective in assessing application Usability, providing valuable feedback for developers to enhance Samagov’s functionality and ensure it meets user need.